Antibiotic stewardship and antimicrobial resistance in conflict-affected Sudan: a situational analysis - Fletcher, Megan; Trueba, Mei; Al-Hassan, Leena (Frontiers in Public Health, 2025)
IntroductionAntimicrobial resistance (AMR) is a global concern, the drivers and consequences of which are exacerbated by poverty and inequality, with Low- and Middle-Income Countries (LMICs) bearing the highest rates, particularly Sub-Saharan Africa. Armed conflict further exasperates problem, by damaging healthcare systems, limiting access to essential medicines, and increasing the use of antibiotics in uncertain environments. This study sought to explore healthcare professionals’ views on AMR and antimicrobial stewardship challenges before and during the conflict to investigate the impact of armed conflict on antimicrobial stewardship (ASP) in Sudan, a low-income country facing a humanitarian crisis exacerbated by ongoing violence.MethodsData was collected via an anonymous qualitative online survey completed by healthcare workers with experience before and during the conflict and was analysed via thematic analysis.ResultsSudan is experiencing significant challenges due to its fragile healthcare system, poverty, and inequality. The results identify barriers to ASPs before and during the conflict, including lack of laboratory facilities, inadequate training, and the indiscriminate use of antibiotics. The findings reveal that the conflict has intensified the risk of AMR, with disrupted healthcare services leading to increased self-medication and reliance on broad-spectrum antibiotics.DiscussionThe study underscores the urgent need for multi-faceted interventions that address immediate healthcare needs while implementing long-term strategies to control AMR in conflict-affected regions. Recommendations include enhancing healthcare infrastructure, improving diagnostic capabilities, and fostering collaborations among various stakeholders to ensure sustainable AMR prevention strategies.